The Relationship between iPad Usage and Learning Motivation of Faculty of Medicine Students of Universitas Pasundan - Lestari, Gianita Yulia; Fadhil, Muhammad; Gunadi, Helmi Rosa; Irvan, Firla Rachmani (STKIP Paasundan Press, 2023)
Education can be achieved optimally if a learning process is carried out and given effectively and efficiently. The use of gadgets among students is a habit or a necessity to have, such as cellphones, tablets, and various other types of gadgets. The purpose of this study was to determine the relationship between the use of gadgets and the learning motivation of students at the Faculty of Medicine, Universitas Pasundan. This research is a quantitative research. The sample in this study were 138 students of the Faculty of Medicine, Universitas Pasundan. The sample technique used is nonprobability sampling. The data analysis used was univariate and bivariate analysis. The results of the study show that the relationship between iPad use and learning motivation has a significant relationship with a significance value of >0.05. This is evidenced in the chi-square (χ2) calculation results with a probability value (p-value) that is 0.001 less than 0.05. Thus it can be concluded that there is a relationship between the use of iPAD and student learning motivation at the Faculty of Medicine Universitas Pasundan.